Development of high quality unsweetened kalamansi-orange juice drink - Juanson, Mary Rose Bulos
The increasing demand for fruit juices and the availability of raw materials had led the researcher to develop the kalamansi-orange juice drink in this study. The juice drink produced may become one the alternative drinks to carbonated soft drinks (CSD) which seem to have various ill-effects. Kalamansi-orange juice drink was produced using fresh fruits as raw materials. 50 parts of kalamansi juice and 50 parts of orange juice were blended prior to dilution. The blended juice was divided into three groups and diluted with one part, two parts and three parts water. These were subjected to sensory evaluation. Determination of the most acceptable formulation for the juice drink was done by producing 25:75, 50:50 and 75:25 kalamansi: orange juice rations and subjecting the samples to sensory and physico-chemical analyses. Thermal processing under three different temperatures: 60°C, 70°C and 80°C was done afterwards. The processed juice drinks were examined microbiologically to test the efficiency of the thermal process. Further characterization was done through sensory and physico-chemical analyses. The juice drink diluted with two parts of water was evaluated as having better sensory characteristics than the others. As for the most acceptable formulation for the juice drink, 25:75 kalamansi: orange juice ratio was chosen. This was based on the results of the sensory evaluation. Microbiological examination confirmed that the juice blend should be processed at 80°C to produce lesser microbial count. Characterization of the juice drink suggested that the product was found to have a yellow-orange color, has sour but distinct sweet flavor and is generally acceptable to the panelists.